The Online Learning Experience of Theology Students in Turkey during the COVID-19 Pandemic: A New Disposition for RE? - Selçuk, Muallâ (Religious education, 2021)
Through a quantitative research model, this study aims to understand the general attitudes of theology students in Turkey regarding online learning during the COVID-19 pandemic. In examining the determinant factors on their attitudes, research findings include: previous online education experience, the frequency of participating in synchronous courses, the qualifications of the instructor, the assessment and evaluation procedures, the orientation training programs and the infrastructure opportunities of the universities. Interpreting these factors enables the authors of this article to suggest a conversational relationship between RE and Islamic sciences with some shared objectives that leads to naming guiding principles in a manner that significantly supports students’ vocational journey.